Pengaruh Pemberian Air Cucian Beras Terhadap Produktivitas Jamur Merang (Volvariella volvaceae) Pada Media Bonggol Jagung - Elawati, Nunung Eni; Dewi, Sintia Puspa (Indonesian Journal of Biomedical Science and Health; Vol 1 No 1 (2021): Agustus 2021DO - 10.31331/ijbsh.v1i1.1837, 2021)
The production of edible mushroom (Volvariella volvaceae) is strongly influenced by the media. The media is in the form of organic waste, such as corn cobs and rice washing water. The purpose of this study was to determine the productivity of edible mushroom growing on corncob media with different concentrations of rice washing water. This study used a completely randomized design (CRD) consisting of 6 treatments, namely K0 (without rice washing water), K1 (20 ml rice washing water + 80 ml aquadest), K2 (40 ml rice washing water + 60 aquadest), K3 (60 ml of rice washing water + 40 ml of aquadest), K4 (80 ml of rice washing water + 20 ml of aquadest), K5 (100 ml of rice washing water without aquadest). The observed variables were fruit body length, number of fruit bodies, and mushroom fruit weight. The data were analyzed using One Way ANOVA with a level of 5%, then Duncan's test was continued to find out the best treatment. The results showed that there was a significant effect on the number of fruit bodies and fruit body weight, but not significant on the length of the mushroom fruit bodies on corncob media and different concentrations of rice washing water. The optimal provision of rice washing water for mushroom growth is a concentration of 80 ml